2018
DOI: 10.1097/md.0000000000013169
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of clinical trials comparing the efficacy and safety of liposomal cisplatin versus conventional nonliposomal cisplatin in nonsmall cell lung cancer (NSCLC) and squamous cell carcinoma of the head and neck (SCCHN)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…First, platinum‐compounds are being formed with novel attached side groups (eg, phenanthriplatin), which cause diverse DNA adducts less susceptible to known mechanisms of drug resistance. Second, new platinum formulations have been developed that alter drug pharmacokinetics, such as liposomal cisplatin, which has been purported to be less neurotoxic . Finally, platinum drugs are being conjugated with bioactive compounds in order to increase efficacy and better target cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First, platinum‐compounds are being formed with novel attached side groups (eg, phenanthriplatin), which cause diverse DNA adducts less susceptible to known mechanisms of drug resistance. Second, new platinum formulations have been developed that alter drug pharmacokinetics, such as liposomal cisplatin, which has been purported to be less neurotoxic . Finally, platinum drugs are being conjugated with bioactive compounds in order to increase efficacy and better target cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (CP) is a chemotherapeutic drug that has been used clinically for decades in patients with malignant tumors; however, nephrotoxicity, which is the major side effect of CP treatment, has greatly limited its application as a treatment ( 1 , 2 ). Thus, there is an urgent requirement to develop a novel therapeutic agent that protects against CP-induced renal injury and obtain novel insights into the treatment of patients with cancer undergoing CP-based chemotherapy regimens ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Canta et al, 2011, showed that lipoplatin, a liposomal formulation of cisplatin, reduced the systemic toxicity of cisplatin; and this formulation was markedly less nephrotoxic and induced less neurotoxicity than conventional cisplatin [ 30 ]. There are data that show that lipoplatin does not cause damage to the proximal kidney tubules as does cisplatin for several reasons: cisplatin remains protected by the lipid capsule, and the entrance of lipoplatin particles into the kidney tubule cells is limited; additionally, lipoplatin is released through the kidney with a half-life of 60–117 h compared to 6.5 h for conventional cisplatin, these pharmacokinetic differences could also explain the low renal toxicity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%